A Psycholinguistic Analysis of Semantic Transfer by Turkish Learners of English - Sönmez-Boran, Görsev (Araştırmacı Çocuk Merkezi, 2018)
This study examines the proposition that second language learners tend to map second language (L2) lexical forms onto the existing semantic content of their first language (L1) translations rather than creating a separate semantic network for the second language. To test this, the participants (n=9) responded to three semantic judgement tasks. In the first task, they were asked to state whether the English words can be used interchangeably or not (experiment 1). In the second task, they were provided the words and asked to place them into suitable sentences. Finally, they were given a forward translation task (task two and three are involved in experiment 2). Results showed that older foreign language learners bring their already developed conceptual and semantic systems which demonstrates that the participants are highly influenced by their native language. Additionally, an undeniable effect of context on the students’ performance was observed in the results.In line with these results, the implications were discussed within the psycholinguistic perspective and semantic transfer hypothesis.

Bu çalışma, ikinci dil öğrenenlerinin, ikinci dil için ayrı bir anlamsal ağ oluşturmaktan ziyade, ikinci dil (L2) sözcük formlarını ilk dildeki (L1) çevirilerin mevcut semantik içeriğine yerleştirme eğiliminde oldukları önermesini incelemektedir. Bunu yaparken, katılımcılar (n = 9) üç semantik yargı görevine yanıt verdi. İlk görevde, İngilizce sözcüklerin birbirinin yerine kullanılıp kullanılamayacağına yanıt vermeleri (deneme 1) istendi. İkinci görevde verilen kelimeleri uygun cümlelere yerleştirmeleri istendi. Sonunda, bir ileri çeviri görevi verildi (görev 2 ve üç deney 2'de yer aldı).Elde edilen sonuçlar, yaşça büyük olan yabancı dil öğrenenlerin, geliştirdikleri kavramsal ve semantik sistemleri beraberlerinde getirdiklerini ve katılımcıların ana dilden çok etkilendiğini göstermektedir. Buna ek olarak, bağlamın öğrencilerin performansı üzerindeki yadsınamaz etkisi, sonuçlarda açıkça görülmüştür. Bu sonuçlar doğrultusunda sınıf içi uygulanabilirliği psikodilbilimsel bakış açısı ve anlamsal aktarım hipotezi açısından tartışılmıştır.
Keywords: Psikodilbilim; ikinci dil